2014
DOI: 10.3390/challe5020338
|View full text |Cite
|
Sign up to set email alerts
|

Forest Biomass for Energy Production: Perceptions of State Forestry Professionals from China and India

Abstract: This study investigated perceptions of a group of Chinese and Indian state forestry professionals (SFPs) related to the potential benefits and challenges of developing forest-based bioenergy projects (FBPs) in their countries. A total of 110 SFPs participated in the study (55 from each country). The results showed that the SFPs widely agreed upon the potential economic and ecological benefits from developing FBPs in their countries. The economic benefits of job creation and additional income to forest departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Among these, woody biomass is obviously attractive to those rural communities with access to an abundant supply of forest resources. The utilization of woody biomass for energy offers several key benefits, including job creation, an additional income source for the forestry sector [1], mitigating global warming, and securing a stable energy supply. Moreover, using renewable biological resources for energy contributes to promoting the creation of a bioeconomy [2].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, woody biomass is obviously attractive to those rural communities with access to an abundant supply of forest resources. The utilization of woody biomass for energy offers several key benefits, including job creation, an additional income source for the forestry sector [1], mitigating global warming, and securing a stable energy supply. Moreover, using renewable biological resources for energy contributes to promoting the creation of a bioeconomy [2].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the use of woody biomass to solve the needs of residential heating allows to reduce dependence on fossil fuels and to mitigate climate change. These results provide new perspectives on sustainable development in rural communities [11] [12].…”
mentioning
confidence: 99%